2020
DOI: 10.1108/ijchm-06-2020-0546
|View full text |Cite
|
Sign up to set email alerts
|

Importance of F&B operation in luxury hotels: the case of Asia versus the US

Abstract: Purpose This paper aims to understand the effect of food and beverage (F&B) services on the operating performance of luxury hotels and to identify the heterogeneous effects of the luxury hotels’ F&B operation on the business performance between Asia and the USA. Design/methodology/approach Operating performance of luxury hotels in Asia (37 hotels), including Japan, Singapore, South Korea and Hong Kong and in the USA (72 hotels), including New York, California, Florida, Illinois and Texas was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Ramanathan et al (2016) find that diversification strategy does not impact on the performance in the UK hotel industry. Mun et al (2020) find that the effect of food and beverage services on the operating performance of luxury hotels is heterogeneous between Asia and the USA. Chen and Chang (2012) also find for a sample of Taiwanese hotels that those that offered food and beverages obtained greater benefits than those that simply offered accommodation, albeit at the cost of greater variability in the benefits.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Ramanathan et al (2016) find that diversification strategy does not impact on the performance in the UK hotel industry. Mun et al (2020) find that the effect of food and beverage services on the operating performance of luxury hotels is heterogeneous between Asia and the USA. Chen and Chang (2012) also find for a sample of Taiwanese hotels that those that offered food and beverages obtained greater benefits than those that simply offered accommodation, albeit at the cost of greater variability in the benefits.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 95%
“…(2016) find that diversification strategy does not impact on the performance in the UK hotel industry. Mun et al . (2020) find that the effect of food and beverage services on the operating performance of luxury hotels is heterogeneous between Asia and the USA.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Notably there have been a strand of nascent research studies conducted particularly on Malaysia, in exploring the adoption of digital wallet electronic payment system using varied of technology adoption model and myriad of explanatory constructs. Mun et al (2021) explored the adoption of e-wallet using an extended TAM model; the study found that all casted construct (perceived usefulness, perceived ease-of-use, perceived credibility and social influence) to have a significant effect on of behavioural intention, case in point the most significant predictor was perceived usefulness. Following the same narrative, Karim et al (2020) found that perceived usefulness and perceived ease of use, with addition of privacy and security has significant effect on behavioural intention which positively support e-wallet use; a similar result was attain by Alaeddin et al (2018).…”
Section: Review Of Literature and Motivationmentioning
confidence: 99%
“…Therefore, as previously summarized, food and beverages can be a valued attribute for clients in hotels, but rarely breakfast has been studied determining guests' options when choosing their accommodation. Breakfast is a meal that is part of the hotel's food service and that can be decisive in choosing one accommodation unit over another according to Mun and Seo (2020), in addition to which a good breakfast can positively affect other services provided by the hotels (Tophotelnews, 2021).…”
Section: Literature Review the Importance Of Food And Breakfast When ...mentioning
confidence: 99%